Evidence for magnetic clusters in Ni1-xVx close to the quantum critical concentration. (18th March 2015) - Wang, R; Ubaid-Kassis, S; Schroeder, A; Baker, P J; Pratt, F L; Blundell, S J; Lancaster, T; Franke, I; Möller, J S; Vojta, T
Abstract: The d-metal alloy Ni1- x V x undergoes a quantum phase transition from a ferromagnetic ground state to a paramagnetic ground state as the vanadium concentration x is increased. We present magnetization, ac-susceptibility and muon-spin relaxation data at several vanadium concentrations near the critical concentration xc ~ 11.6 % at which the onset of ferromagnetic order is suppressed to zero temperature. Below xc, the muon data reveal a broad magnetic field distribution indicative of a long-range ordered ferromagnetic state with spatial disorder. We show evidence of magnetic clusters in the ferromagnetic phase and close to the phase boundary in this disordered itinerant system as an important generic ingredient of a disordered quantum phase transition. In contrast, the temperature dependence of the magnetic susceptibility above xc is best described in terms of a magnetic quantum Griffiths phase with a power-law distribution of fluctuation rates of dynamic magnetic clusters. At the lowest temperatures, the onset of a short-range ordered cluster-glass phase is recognized by an increase in the muon depolarization in transverse fields and maxima in ac-susceptibility.